2017
DOI: 10.1007/s00284-017-1294-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Intestinal Microbiota of Gibel Carp (Carassius gibelio) Associated with Cyprinid herpesvirus 2 (CyHV-2) Infection

Abstract: Gut microbiota are integral to the host, and have received increased attention in recent years. However, information regarding the intestinal microbiota of many aquaculture animals is insufficient; elucidating the dynamics of the intestinal microbiota can be beneficial for nutrition, immunity, and disease control. In this study, we used 16S rRNA sequencing to observe changes in the intestinal microbiota of gibel carp (Carassius auratus gibelio) associated with cyprinid herpesvirus 2 (CyHV-2) infection. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Regardless, similar changes have been documented in a wide range of infections and hosts ranging from pulmonary tuberculosis in humans [ 31 ], to Cryptosporidium intestinal infection in lower primates [ 32 ], to herpesvirus infection in fish. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, similar changes have been documented in a wide range of infections and hosts ranging from pulmonary tuberculosis in humans [ 31 ], to Cryptosporidium intestinal infection in lower primates [ 32 ], to herpesvirus infection in fish. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Grass carp infected by GCRV always show damaged endothelial and blood cells, resulting in platelet activation and aggregation, haemolysis, and inflammatory responses (Meri, 2013). We found that the alpha‐diversity of gut microbiota in the diseased grass carp was significantly lower than that of controls, which is consistent with virus diseases in gibel carp challenged by Cyprinid herpesvirus (She et al ., 2017). A viral infection may promote extensive immune reaction against viruses, a failure of properly calibrate immune responses will further result in confrontations to commensal bacteria, thus decrease the alpha‐diversity.…”
Section: Discussionmentioning
confidence: 99%
“…We have much less understanding of fish immune responses to a dysbiosis of gut microbiota initiated by virus invasion (Nie et al ., 2017; Xiong et al ., 2019). Although the infection of cyprinid herpesvirus 2 (CyHV‐2) in gibel carp could decrease the diversity of intestinal microbiota (She et al ., 2017), and fish gut microbiota are also found to be closely correlated with host immunity (Stagaman et al ., 2017; Murdoch and Rawls, 2019), how microbial disturbances influence fish immune response remains unknown (Gómez and Balcázar, 2008; Nie et al ., 2017). Understanding and manipulating gut microbiota may be a new direction to improve fish health and production (Dimitroglou et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Genus Flavobacterium is Gram-negative, rod-shaped, non-motile and motile bacteria, and they have been reported in the GI tract of several fish species [34,35,[41][42][43], but several species are known to cause disease in fish [44,45]. Flavobacterium sasangense BA-3, an autochthonous intestinal strain isolated from common carp (Cyprinus carpio), has been suggested as probiotics [21].…”
Section: Flavobacteriummentioning
confidence: 99%